Wie fühlen sich die Menschen in Ost- und Mittel-Europa? Welche Werte verfolgen sie? Fragmente aus der sozialwissenschaftlichen Werteforschung - Tomka, Miklós (European Journal of Mental Health, 2011)
How do People in Eastern and Central Europe Feel? What Values do They Follow? Fragments from Sociological Values Research: The post-socialist countries in Eastern and Central Europe carried different firmly ingrained habits, traditions and social mechanisms into the era following the political turn in 1989. These differences have slowed down the spiritual coalescence of the Old Continent. The study describes the various emotional attitudes and value conceptions with the help of sociological values research and relevant literature. Its aim is to show how the political relations that evolved in the eastern regions of Europe in the decades following World War II have been affecting the relationship of citizens to the state and each other ever since. Of the challenges related to the need for modernisation and facing the new democracies in the region, the analysis emphasises the great weight of the agricultural sector, the underdevelopment of industry and the poor economic performance on the one hand and the tumbling of the former social order as well as the immaturity of civil society on the other. Then it goes on to show how individualism and retreat into the private sphere (patterns that were fostered by communist party politics) are still influencing social life today. At the same time, in the society of wealth and excess the attribute of highest good is assigned to such ‘post-material’ values as freedom, the environment, human rights and equality. Finally, the study discusses the different political opinions and value conceptions resulting from an unusual course of development, the feeling of nostalgia towards communism, social differentiation and the prestige loss of the ‘working class’.